2020
DOI: 10.1055/s-0040-1718580
|View full text |Cite
|
Sign up to set email alerts
|

Improving Utilization of Aspirin for Prevention of Preeclampsia in a High-Risk Urban Cohort: A Prospective Cohort Study

Abstract: Objective This study aimed to evaluate the utilization of aspirin for preeclampsia prevention before and after implementation of a screening tool during nuchal translucency (NT) ultrasound. Study Design One-year prospective cohort study of patients at high risk for preeclampsia after the implementation of a screening tool (postscreen) administered to all patients at check in for NT (11–13 weeks) ultrasound. Prospective cohort was compared with one-year retrospective cohort (prescreen) the year prio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 18 publications
3
10
0
Order By: Relevance
“…17,18 However, similar to our study, Boelig et al showed that the implementation of a clinical checklist improved provider LDA recommendation to 95%. 18 Our study has some limitations. We do not know how the counseling style differed among physicians and whether patients responded differently to different counseling styles.…”
Section: Strength and Weaknesssupporting
confidence: 87%
“…17,18 However, similar to our study, Boelig et al showed that the implementation of a clinical checklist improved provider LDA recommendation to 95%. 18 Our study has some limitations. We do not know how the counseling style differed among physicians and whether patients responded differently to different counseling styles.…”
Section: Strength and Weaknesssupporting
confidence: 87%
“…A second study, by Boelig and colleagues, assessed provider adherence to aspirin recommendations before and after implementation of a preeclampsia risk assessment tool designed to help identify at-risk women. (Boelig et al, 2020) The study analyzed only prescribing rates for women with one or more "high" risk factor, and did not assess rates for women with multiple "moderate" risk factors. They found that prior to implementation of the screening tool 74% of eligible women were recommended aspirin prophylaxis, compared to 95% following this intervention.…”
Section: Conclusion For Practicementioning
confidence: 99%
“…Our findings suggest a potentially actionable, common (~10%–15% of general population, 23 30% of Black individuals), genetic variant that may contribute to disparate response to aspirin therapy 20 and risk of preterm birth. Prior studies at our institution have demonstrated a persistently high (~30%) rate of preeclampsia in high‐risk populations despite aspirin therapy 44,45 20 .…”
Section: Results In the Context Of What Is Knownmentioning
confidence: 91%
“…Prior studies at our institution have demonstrated a persistently high (~30%) rate of preeclampsia in high-risk populations despite aspirin therapy. 44,45 Studies on PAR4Thr120 variant in nonpregnant adults identify a reduced response to antiplatelet therapies. 20 The potential pharmacogenomics implications of the optimal antiplatelet therapy formulation and dose to reduce that risk in individuals homozygous for PAR4Thr120 needs to be studied prospectively.…”
Section: Clinical and Research Implicationsmentioning
confidence: 99%